Modification of the chemical structure and the wear-resistance improvement of semifritted glaze of floor ceramic tiles by addition of fused corundum - Anufrik, Slawomir S.; Kurian, Nikolai N.; Znosko, Casimir F.; Zhukova, Irina I. (Journal of the Belarusian State University. Physics, 2017)
Using the techniques of X-ray fluorescence (XRF) and laser emission (LIBS) spectral analysis, the chemical composition of the finished semifritted glaze for floor tiles and its components (dyes of the brands 13/400, 10/195, glazes, and corundum) have been studied. A comparative analysis of the results obtained by these methods has been performed. With the help of the LIBS technique, the element chemical composition (Si, O, Mg, C, H, N) revealing the vegetable origin of the dye 10/195 has been established. By the XRF method in the control sample of ceramic tiles 24 chemical elements were identified; the concentrations of the main chemical elements (S, Ca, Fe, K, Ba, Zr, Ti, Cl), macro- (Hg, Rb, Cd) and microimpurities (Pb, V, Sn, Zn, Br, Sr, Sb, Mn, Cu, Mo, Cr, Co, As) were determined with a measuring error of about 1 %. It has been shown that the addition of corundum in optimal concentrations (16 %) allows one to increase significantly the wear resistance and roughness of the semifritted glaze for floor ceramic tiles.